Eclipse of the crown eaudiobook - Caggiano, A. K. (Villains and Virtues, 2024)
Their destinies are irrevocably entangled, but will their bond be the realm's undoing? Damien and Amma have landed themselves in the midst of Yvlcon, the preeminent congregation of the vilest and most unscrupulous villains in existence. Once again amongst his peers, Damien's moral growth is threatened just when he's learning to be slightly less evil. Consequently, Amma finds her own virtue in peril when faced with so much temptation, namely in the form of a domineering blood mage she can't—or doesn't want—to say no to. But a burgeoning romance is doused in the coldest of baths when the Grand Order of Dread commands Damien to once again face the swirling vortex of entropy that's been hunting them all over the realm. The coming eclipse points to devastation and destruction, and there seems to be no avoiding annihilation, prophecy being, well, prophecy, after all. But there's an entire fortnight before the world is supposed to end, and surely that's enough time to find some way around it, or to at least confess one's devotion to the other before it all burns down around them.